An assessment of contemporary glacier fluctuations in Nepal’s Khumbu Himal using repeat photography - Byers, Alton C (Himalayan Journal of Sciences, 2008)
A preliminary study of glacial fluctuations in Sagarmatha (Mt Everest) National Park, Nepal was undertaken in Oct–Nov 2007 using repeat photography. Photographs from scientific and cartographic expeditions to the upper Imja Khola region ca. 1950 were replicated in order to derive a better, empirically-based understanding of what changes had occurred in the region’s glaciers during the past half century. Over 40 distinct panoramas were replicated which demonstrated the (a) complete loss of certain small (< 0.5 km2), clean glaciers (C-Type) between approximately 5400–5500 masl, (b) the retreat of larger (>0.5 km2) clean glaciers by as much as 50 percent of the ca. 1955 volumes at elevations ranging from approximately 5500–5600 masl, (c) the formation of new and potentially dangerous glacial lakes that had been debris covered glaciers (D-Type) in the 1950s, and (d) the ablation of most of the D-Type glaciers re-photographed. The findings support and complement those of recent investigations based almost entirely on remote sensing and computer modelling. However, detailed, on-the-ground field studies of potential climate change impacts on the people and environments of the Mt. Everest region are disturbingly absent. I suggest that only by systematically combining field and laboratory-based investigations will we acquire the tools to enable us to identify the real threats, non-threats, and ways in which local people can adapt and reduce vulnerabilities to climate change. Himalayan Journal of Sciences Vol.4(6) 2007 p.21-26